Drug nanocarriers to treat autoimmunity and chronic inflammatory diseases. (December 2017) - Prosperi, Davide; Colombo, Miriam; Zanoni, Ivan; Granucci, Francesca
Abstract: Nanoparticles represent a new generation of drug delivery systems that can be engineered to harness optimal target selectivity for specific cells and tissues and high drug loading capacity, allowing for improved pharmacokinetics and enhanced bioavailability of therapeutics. The spontaneous propensity of both organic and colloidal nanoparticles to be captured by the cells of the reticuloendothelial system encouraged their utilization as passive targeting systems that can be preferentially directed to innate immune cells, such as macrophages, dendritic cells and neutrophils. The natural affinity for phagocytic cells suggests the possible implementation of nanoparticles as an immunotherapeutic platform for inflammatory diseases and autoimmune disorders. Here we discuss the recent advances in the application of nanotechnology to induce antigen-specific tolerance in autoimmunity and the use of nanoparticles for anti-inflammatory therapies, including treatment of inflammatory bowel diseases, psoriasis and rheumatoid arthritis.